Foreign Policy of Nepal: Understanding on Bilateral, Regional and Multilateral Relations of House of Representatives, GoN (Janapriya Journal of Interdisciplinary Studies, 2025)
The research article “Foreign Policy of Nepal: Understanding on Bilateral, Regional and Multilateral Relations of House of Representatives, GoN” underscores fundamentally examine and critically analysis the perception and knowledge of the respondents on international relations, foreign policy and diplomacy. The research is based on quantitative research method that reflects the understanding of the respondents 2080 -2082 B.S, to measure the understanding on foreign policy, regarding bilateral, regional and multilateral relations in international relations based on foreign policy of Nepal. In this regard, primary data has been use; thus, the primary data has been collected, analyzed and interpreted. The reason behind conducting the research on this topic is to generate the basic understanding and analyze the reason how Nepal positions herself diplomatically in the international arena based on foreign policy. Paradigm: The research philosophy is under pragmatism followed by the inductive research approach. The methodological choice is based on quantitative and the survey research strategy in application. The researcher gathers primary data through purposive sampling; it is the main source of data collection and the data analysis is based on quantitative data analysis using SPSS software. The finding reveals a significant understanding of the respondent’s calibrated to formulate the diplomatic execution on bilateral, regional and multilateral relations of Nepal.